ULTRASOUND GUIDED PREDICTION OF DIFFICULT TRACHEAL INTUBATION: AN OBSERVATIONAL STUDY - Dr. Ifra Abid; Dr. Sana Khan; Dr. Annam Qayoom (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Ultrasonography has emerged as a new airway assessment tool. Unanticipated difficult intubation remains a primary concern for anaesthesiologists. Theoretically, accurate preoperative airway evaluation can reduce or avoid unanticipated difficult intubation.Aim: To evaluate the accuracy of pre‑operative ultrasound assessment of the neck in predicting difficult airways  in patients undergoing elective surgery under general anaesthesia.Methods: 40 patients with BMI (30kg/m-2) and ASA Grade II and III both sexes, aged between 18 and 70 years, scheduled for different surgeries under general anaesthesia were included in this prospective observational study conducted  at the SMHS Hospital which is one of the associated hospitals of Government Medical College Srinagar. Patients selected for surgery were admitted at least 24 hours prior to surgery. The attending anaesthetist evaluate the following variables pre operatively: history of snoring and OSAS, Modified Mallampati score (MMS), loose or protruding upper teeth or partially missing upper incisors or canines; thyromental distance, TM joint mobility, neck mobility, body mass index, neck circumference at the level of thyroid cartilage and USG measurements of anterior neck soft tissue thickness was obtained at three levels.Results: Mean weight of 68.40±8.15kg in the patients with difficult intubation while as mean weight of 61.50±9.25 among the patients with easy intubation with statistically significant difference among the study population (p